SUDUT PANDANG WAJIB PAJAK UMKM TERHADAP KEWAJIBAN PERPAJAKAN PERATURAN PEMERINTAH NO 23 TAHUN 2018 (STUDI PADA UMKM DI KEMAYORAN JAKARTA PUSAT - Fungsiawan; Nurmadhani Fitri Suyuthi; RR Dian Anggraeni; Adibah Yahya; Intan Dyah Pravita (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2022)
This study aims to determine the effect of the MSME taxpayer's point of view on the tax obligations of government regulation no. 23 of 2018 (study on MSMEs in Kemayoran, Central Jakarta. This study uses a simple linear regression method by measuring the implementation of MSMEs by meeting the requirements required for taxation. MSMEs are not financial institutions.The results of this study indicate that if it is comprehensive from a mandatory point of view from taxation, from clear insight and knowledge up to 0.05%, the aspect of tax knowledge and mandatory value is the difference, there is no different reference regarding obligatory or taxation.